2017
DOI: 10.1177/2050640616646525
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload correlates with serum liver fibrotic markers and liver dysfunction: Potential new methods to predict iron overload‐related liver fibrosis in thalassemia patients

Abstract: Background: Early detection of liver fibrosis in thalassemia patients and rapid initiation of treatment to interfere with its progression are extremely important. Objective: This study aimed to find a sensitive, easy-to-detect and noninvasive method other than liver biopsy for early detection of liver fibrosis in thalassemia patients. Methods: A total of 244 Chinese Thalassemia patients with non-transfusion-dependent thalassemia (NTDT, n ¼ 105) or thalassemia major (TM, n ¼ 139) and 120 healthy individuals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…Intensified liver Fe uptake may lead to hepatic Fe overload [50]. It was shown that liver iron overload was associated with elevated blood levels of ALT [51]. However, in our previous studies, we did not find this relationship [47,49].…”
Section: Introductioncontrasting
confidence: 57%
“…Intensified liver Fe uptake may lead to hepatic Fe overload [50]. It was shown that liver iron overload was associated with elevated blood levels of ALT [51]. However, in our previous studies, we did not find this relationship [47,49].…”
Section: Introductioncontrasting
confidence: 57%
“…The ages of the patients and control groups were distributed between 1 year to 44 years. The more significant majority of the infected persons with HCV was in the middle age groups (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years old, while the lowest rate of infected persons was in the age group (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) years of old. Gender did not differ significantly among thalassemia patients with or without HCV infection and healthy subjects (Table2).…”
Section: Molecular Rt-pcr Resultsmentioning
confidence: 99%
“…At a global level, between 4.4 % and 85.4 % of the thalassemia patients are positive for anti-HCV antibodies 18 . The distribution of patients according to age were as follow: 73.0% were in the range of (15-29) years; 18.0% in the range (1-14) yearsand 9% inthe range (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) years. In our study, the mean age of thalassaemic patients with anti-HCV was20±7.0 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations